Relationship between macroeconomic variables and net asset value (NAV) of Islamic equity unit trust funds: cointegration evidence from Malaysian unit trust industry - Othman, Anwar Hasan Abdullah; Mydin Meera, Ahamed Kameel; Abd. Aziz, Hassanuddeen (Global Academy of Training & Research (GATR) Enterprise, 2013)
Objective – Even though the unit trust industry witnessed high growth in portfolios size, performances and regulations, however, there is still insufficient understanding of various aspects of the industry such as the lack of information on the funds’ unit price behavior and their trend in the long-term investment. This study, therefore, aims to investigate the long- run relationship between the chosen macroeconomic factors and the NAV of the Islamic equity unit trust funds as well as the effect of the (2007-2008) global financial crisis on the performance of Islamic equity unit trust funds and their unit prices. Methodology/Technique – The study utilized Vector Autoregression (VAR) framework in order to analyze this relationship over the period January 2006 to December 2012 using monthly data. Findings – The findings of the investigations confirmed that the selected macro-economic variables do share long-run relationship with the NAV of the Islamic equity unit trust funds in the Malaysian capital market. Novelty – A successful innovation of the relationship between the funds NAV and the selected macroeconomic variables will assist the entire interested group, such as, investors, management of the funds, government agencies, industry players and policy makers to estimate the future trend direction of the NAV and accordingly decide on the operational, managerial, and sustainable growth decisions.